Comparison of two skin temperature assessment methods after the application of topical revulsive products: Conductive iButton data logger system vs contact‐free infrared thermometry. Issue 5 (9th April 2020) - Stoop, Rahel; Hohenauer, Erich; Aerenhouts, Dirk; Barel, André O.; Deliens, Tom; Clijsen, Ron; Clarys, Peter
Abstract: Background: Skin temperature assessments comprise conductive and contact‐free techniques. Comparison between conductive data loggers and contact‐free thermometry after the application of revulsive products is scarce. This study aimed to compare iButton data loggers with an infrared thermometer after the application of two revulsive products. Secondly, the relation between skin temperature kinetics with skin's perfusion of microcirculation was investigated. Materials and methods: Healthy females (n = 25) were randomly allocated to two groups, representing the products A and B. Skin temperature was measured with "iButtons" and an infrared pistol at baseline and up to 1 hour after application. Skin's perfusion of microcirculation was monitored with a laser speckle contrast imager. Results: Baseline "iButton" temperature values were significantly lower compared with infrared pistol values in both groups. After application of the products, skin temperature decreased as recorded with both devices followed by an increase to baseline values when measured with the pistol. The results obtained by the "iButtons" reached values above baseline in both products towards the end of the follow‐up period. A moderate correlation was found between infrared pistol and "iButton" system in product A, with a weak negative correlation between skin's perfusion of microcirculation and temperature devices. For product B, the correlation between the devices was moderate and between skin's perfusion and temperature devices weak and positive. Conclusion: Both devices produced similar kinetics, except at baseline, where they may differ as metallic loggers have been insufficiently adapted to skin temperature. Skin's perfusion of microcirculation could not explain skin temperature changes.